H HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN SKABIES DI PANTI ASUHAN UJUNGGURAP TAHUN 2018 - mastiur napitupulu; Sri Darmini Pulungan (CHMK NURSING SCIENTIFIC JOURNAL, 2020)
ABSTRACT Scabies is a disease of significant public health significance as it is a substantial contributor to global morbidity and mortality. a factor in the high prevalence of scabies related to personal hygiene.The purpose of this study was to see the relationship between personal hygiene and the incidence of scabies. This type of research is in the form of an observational survey with a case-control approach. The research was conducted In ujung gurap orphanage. The study population was 150 people with a sample of 76 people (38 people in the case group and 38 people in the control group). The sampling technique uses "random sampling". Analysis of the data used is chi-square. The results of the study showing a Relation of significant between personal hygiene and the occurrence of scabies p=0.005 (p < 0,05), OR velue 4,293 times (95% CI : 1,625-11,346). To Recommended for orphanages to follow counseling from the health department and other health workers so that orphanages know how to avoid or prevent scabies.